The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1002/jssc.201000160
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of bacterial lipid profiles by using rapid sample preparation and fast comprehensive two‐dimensional gas chromatography in combination with mass spectrometry

Abstract: The bacteria fatty acid profile has been extensively studied for taxonomic classification purposes, since bacteria, in general, contain particular and rare fatty acids, compared with animal and plant tissues. As for any real-world sample type, the development of rapid and reliable methods for (i) sample identification (in this case, bacterium type), and (ii) constituent identification (in this instance, the fatty acid profile) is desirable. In this research, a half-an-hour procedure, to analyze bacteria, was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 18 publications
1
22
0
Order By: Relevance
“…Current GCϫGC-TOF-MS analyzers can operate with very high acquisition rates, typically up to 500 Hz, and offer higher resolution and sensitivity. Recent metabolomics applications of GCϫGC-MS include animals (40), plants (41)(42)(43)(44), microorganisms (45), and other samples such as human serum and tissues (46 -48). Fig.…”
Section: Chromatography Coupled To Msmentioning
confidence: 99%
“…Current GCϫGC-TOF-MS analyzers can operate with very high acquisition rates, typically up to 500 Hz, and offer higher resolution and sensitivity. Recent metabolomics applications of GCϫGC-MS include animals (40), plants (41)(42)(43)(44), microorganisms (45), and other samples such as human serum and tissues (46 -48). Fig.…”
Section: Chromatography Coupled To Msmentioning
confidence: 99%
“…Using such an instrumental configuration, the MS can be used to identify unknown compounds and the FID for quantification purposes. Purcaro et al (2010b) used fast one-step sample preparation for extraction and methylation of bacteria FAs, requiring 2 min, and a relatively rapid split-flow twin-oven comprehensive 2D GCeqMS Two-dimensional chromatogram of menhaden fish oil sample obtained using GC-online hydrogenation  GC-FID. FID, flame ionization detector; GC, gas chromatography.…”
Section: Fatty Acid Analysismentioning
confidence: 99%
“…Often greater resolving power, enhanced peak capacity, and improved sensitivity over 1D GC, obtained by GC × GC supported by unique structured patterns within the retention plane arising from "boiling point" and "polarity" relationships, aid in compound identification [1, 3,10,13,17,19]. These advantages have been applied to the study of biological oils, marine oils, bacterial lipids, and various compounds in environmental and dairy products, and in plant oils [1,4,[19][20][21]. Applications revealed that saturated and unsaturated compounds are located in different regions to permit easier identification of unknown FAMEs in complex matrices.…”
Section: Introductionmentioning
confidence: 99%